2020
DOI: 10.1007/s00203-020-01818-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-associated infections: development of antimicrobial resistance and possible treatment strategies

Abstract: Diabetes mellitus is associated with various types of infections notably skin, mucous membrane, soft tissue, urinary tract, respiratory tract and surgical and/or hospital-associated infections. The reason behind this frequent association with infections is an immunocompromised state of diabetic patient because uncontrolled hyperglycemia impairs overall immunity of diabetic patient via involvement of various mechanistic pathways that lead to the diabetic patient as immunocompromised. There are specific microbes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 123 publications
(101 reference statements)
1
76
1
3
Order By: Relevance
“…Among all listed comorbidities, DM was independently associated with increased antimicrobial usage. DM is a pre-infectious condition and previous studies suggest people admitted at hospitals with DM end up receiving more antibiotics than patients without DM, largely due to the presence of antibiotic resistance gene in the diabetic population [ 13 ]. This finding may have compelled physicians to prescribe multiple antibiotics to make sure the patient's condition does not worsen.…”
Section: Discussionmentioning
confidence: 99%
“…Among all listed comorbidities, DM was independently associated with increased antimicrobial usage. DM is a pre-infectious condition and previous studies suggest people admitted at hospitals with DM end up receiving more antibiotics than patients without DM, largely due to the presence of antibiotic resistance gene in the diabetic population [ 13 ]. This finding may have compelled physicians to prescribe multiple antibiotics to make sure the patient's condition does not worsen.…”
Section: Discussionmentioning
confidence: 99%
“…Infections in DFU are capturing the attention of the clinicians because often related to severe discomfort, increased request of medical cares and high risk of healing failure, which may rapidly lead to hospitalization and lower extremities amputation [5] . The development of diabetic foot infection (DFI) is strictly associated with an open wound [6] , but other risk factors include peripheral neuropathy and arteriopathy, diabetes-related immune dysfunction, renal impairment and the chronic course of the wound itself [6] , [7] . DFI still remains a clinical challenge due to the complexity of medical and surgical treatments and the associated negative outcome.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that reduced levels of IgA in the saliva increase the risk of upper respiratory tract infections (URTI), and vice versa [9,10]. Elderly people, children, and patients with diabetes who have poor immune function are at increased risk of URTI infection [11][12][13]. Therefore, increasing pIgR expression and salivary IgA levels in patients with low immunity are important for URTI prevention.…”
Section: Introductionmentioning
confidence: 99%